Media dan Teknologi dalam Pembelajaran Pendidikan Agama Islam - Ahmad Izzul Haq; Riswan R (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the role and urgency of utilizing media and technology in Islamic Religious Education (PAI) learning as an effort to enhance the effectiveness, relevance, and attractiveness of the learning process in the digital era. The use of media and technology is viewed as a strategic step to integrate Islamic values with contemporary developments and the needs of modern learners. The research method employed is a Systematic Literature Review (SLR) by examining various sources such as books, scientific journals, and research findings related to the application of media and technology in PAI learning. The results indicate that media and technology play an important role in helping teachers deliver PAI materials in a contextual, interactive, and inspiring manner. The utilization of digital technologies, such as instructional videos, online platforms, Islamic applications, and educational social media, can increase students’ motivation, creativity, and engagement in understanding Islamic values. Nevertheless, challenges such as the digital divide, the validity of religious information, and the risk of declining spiritual interaction must also be anticipated. The implications of this study emphasize that PAI teachers need to act as wise and adaptive digital murabbi without losing the essence of Islamic spirituality. Schools are expected to provide support in the form of training, facilities, and a conducive learning environment so that media and technology truly function as tools for da‘wah, character building, and strengthening Islamic values in the modern era.